2019
DOI: 10.2147/ijn.s214236
|View full text |Cite
|
Sign up to set email alerts
|

<p>Surface-Engineered Super-Paramagnetic Iron Oxide Nanoparticles For Chromium Removal</p>

Abstract: BackgroundSuper-paramagnetic iron oxide nanoparticles (SPIONs) are widely used metal nanoparticles for various applications for its magnetic property and biocompatibility. In recent years, pollution of our environment especially with heavy metals in waterbodies has become a major threat and has left us very minimal sources of freshwater to drink. SPIONs or surface modified SPIONs can be used to remove these heavy metalsMethodsSPIONs were synthesized by co-precipitation method and further coated with a biopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Using SEM, the topographical view was visualized at the magnification of 185.93 KX where the synthesized SPIONs were in the size range of 14.53 nm to 20.54 nm (figure 2). Samrot et al (2019c) showed in his earlier discussions the size of SPIONs produced using ammonia as reducing agent was around 25 nm, whereas the use of a different reducing agent in this case Cobalt chloride in NaOH did contribute to the change in size of the…”
Section: Sem-edxmentioning
confidence: 95%
See 1 more Smart Citation
“…Using SEM, the topographical view was visualized at the magnification of 185.93 KX where the synthesized SPIONs were in the size range of 14.53 nm to 20.54 nm (figure 2). Samrot et al (2019c) showed in his earlier discussions the size of SPIONs produced using ammonia as reducing agent was around 25 nm, whereas the use of a different reducing agent in this case Cobalt chloride in NaOH did contribute to the change in size of the…”
Section: Sem-edxmentioning
confidence: 95%
“…Nanotechnology is a blooming field of science and has variety of applications in the field of science (Kreuter et al 2003). Applications of nanoparticles in various fields include agriculture, drug delivery (Samrot et al 2019a), imaging , Justin et al 2018, Sruthi et al 2018, Samrot et al 2018a, mosquito larvicidal activity (Samrot et al 2019b), environmental remediation (Samrot et al 2019c), bioactivity including anticancer and antibacterial activity (Samrot et al 2016, Samrot et al 2018b, Samrot et al 2019a. The increased usage creates demand in the production alleviating the risks associated with improper disposal of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…33 Swarming motility was performed as described before. 10 Antioxidant Assay (DPPH) DPPH solution (0.1 mg/mL) in methanol was prepared. Then, 3 mL of purified polysaccharide (different concentration) was added with 1 mL of DPPH solution.…”
Section: Bioactivities Of Polysaccharides Antibacterial Activitymentioning
confidence: 99%
“…1,2 Their surface area interaction of these nanoparticles leads to unique properties 3,4 and it can be applied in electronics, biomedicine, imaging, environmental remediation etc. [5][6][7][8][9][10] In nanobiotechnology, the recent decade has recorded extensive research on formulation of nanocarriers since they promote easy transport and availability of drug molecules to the targeted site. Nanocarriers are being formulated from both inorganic and organic resources.…”
Section: Introductionmentioning
confidence: 99%
“…Disposal of environmental waste is becoming a significant issue across the world and it majorly polluted water sources and land [1][2][3][4] . The waste byproducts resulting from food processing are keratinous substances including animal hairs, chicken feathers, wool and horns, and vast amounts of certain byproducts are generated yearly.…”
Section: Introductionmentioning
confidence: 99%